Developing reflection on competence-based learning: the Russian experience with the Tuning approach - Anna Serbati; Alessio Surian (Universidad de Deusto, 2014)
The paper focuses on the Tuning Russia project. It aims at providing an overview of the impact of the Tuning methodology and outcomes concerning University teaching, learning, and assessment activities. It identifies: the most relevant results and "lesson learnt" during the project; tools/concepts/experiences that involved teachers found most interesting; strengths and weaknesses; the usefulness of working with colleagues from different Russian universities; and the level of sharing of the Tuning methodology with other colleagues within participating Universities. The empirical data for the study were drawn from a qualitative questionnaire with open questions filled-in by the members of the subject area group "Social Work" involved in the Tuning Russia project. The respondents were six academic teachers from different Russian universities and two European Tuning experts. This reflection by academic teachers upon the initial implementation of the Tuning approach in Russia highlights the opportunities to explore methods of establishing and improving communities of practice in the field of competence-based higher education curriculum development. Results highlight the need to develop further work concerning both summative and formative evaluation in relation to competence-based curricula review in higher education